A Case of Infantile Alexander Disease Accompanied by Infantile Spasms Diagnosed by DNA Analysis - Lee, Jung Mu (The Korean Academy of Medical Sciences, 2006)
Alexander disease (AD) is a rare leukodystrophy of the central nervous system of unknown etiology. AD is characterized by progressive failure of central myelination and the accumulation of Rosenthal fibers in astrocytes, and is inevitably lethal in nature. Symptomatically, AD is associated with leukoencephalopathy with macrocephaly, seizures, and psychomotor retardation in infants, and usually leads to death within the first decade. Its characteristic magnetic resonance imaging (MRI) findings have been described as demyelination predominantly in the frontal lobe. Moreover, dominant mutations in the GFAP gene, coding for glial fibrillary acidic protein (GFAP), a principal astrocytic intermediate filament protein, have been shown to lead to AD. The disease can now be detected by genetic diagnosis. We report the Korean case of an 8-month-old male patient with AD. He was clinically characterized due to the presence of psychomotor retardation, megalencephaly, spasticity, and recurrent seizures including infantile spasms which is a remarkable presentation. Demyelination in the frontal lobe and in a portion of the temporal lobe was demonstrated by brain MRI. Moreover, DNA analysis of peripheral blood showed the presence of a R239L mutation in the GFAP gene, involving the replacement of guanine with thymine.